Emosi Tokoh Utama dalam Novel Sheiland Karya Bayu Permana dan Korelasinya dalam Pembelajaran Sosial Emosional - Piska Piska; Sulastriningsih Djumingin; Baharman Baharman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to: 1) describe the form of emotions of the main character reflected through id in the novel Sheiland by Bayu Permana; 2) describe the emotional form of the main character reflected through the ego in the novel Sheiland by Bayu Permana; 3) describe the form of the main character's emotions reflected through the superego in the novel Sheiland by Bayu Permana; and 4) describe the correlation between the emotional forms of the characters contained in the novel Sheiland by Bayu Permana and social-emotional learning. This research is a qualitative descriptive research using Freud's theory of personality structure, namely id, ego, and superego. Research data in the form of citations in the form of sentences or paragraphs. The source of the data comes from the novel Sheiland by Bayu Permana. The data collection technique is carried out by reading and recording techniques. Data analysis uses the Miles & Huberman model which includes data collection, data reduction, and conclusion drawn. The results of the study show that the various forms of emotions of the main characters reflected through the dynamics of id, ego, and superego show complex patterns of emotion management. Although each personality structure displays a different variety of emotions, there is generally a shift from spontaneous emotional impulses to more mature moral control and judgment. The correlation between the main character's emotional dynamics and social-emotional learning is seen through the way the main character expresses, understands, and manages his emotions in various situations. These emotional experiences reflect the process of developing self-awareness, social awareness, self-management, relational skills, and responsible decision-making. This research provides a scientific contribution by presenting a new perspective on the integration of literary psychoanalysis studies and social-emotional learning, thus opening up opportunities for the use of literary work analysis as a medium to strengthen students' social-emotional competence.